1990
DOI: 10.1111/j.1460-9568.1990.tb00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Comparison of Cell Properties in Cat's Striate Cortex Determined by Different Types of Stimuli

Abstract: Direction and orientation tuning elicited by moving bars, flashing bars and a moving noise field were compared in cells in area 17 of the cat. Fourier analysis of tuning curves (SDO-analysis) was applied to quantify the general sensitivity (S) to visual stimulation, tuning strength to direction(D) and orientation (O), as well as the preferred direction (PD) and orientation (PO). Results from SDO-analysis were compared with the commonly used direction index and half-width-at-half-height orientational tuning par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Wörgötter & Eysel 1987;Wörgötter et al 1990;DeValois & DeValois 1990). These studies provide evidence that generalized stimuli covering large portions of the receptor surface can be well suited to predict responses to specific and/or more spatially restricted stimuli.…”
Section: Physiology Of Ripple Spectramentioning
confidence: 76%
“…Wörgötter & Eysel 1987;Wörgötter et al 1990;DeValois & DeValois 1990). These studies provide evidence that generalized stimuli covering large portions of the receptor surface can be well suited to predict responses to specific and/or more spatially restricted stimuli.…”
Section: Physiology Of Ripple Spectramentioning
confidence: 76%
“…The sharpness of orientational tuning was quantitatively assessed, for a sample of cells dominated by each eye in all strabismic cats, by performing a Fourier analysis of the responses to drifting gratings varied pseudorandomly in drift direction (see Wijrgijtter et al, 1990). Curves were fitted to the data points, taking into account the 0-8th order Fourier components, and tuning widths were calculated.…”
Section: Monocular Response Propertiesmentioning
confidence: 99%
“…It may be predicted that the values for S and O(0) derived with a stationary flashing bar which contains no directional 289 element differ from those values derived with moving bars, due to the superimposition of a directional element on the latter (Worgotter et al 1990). Moving noise fields, and also small moving spots, have been regarded as patterns without an orientational element, i.e., O(0) = 0 (Worgotter et al 1990).…”
Section: Ir(o) --Ir(omentioning
confidence: 90%
“…Recently, based on the periodicity of directional and orientational selectivities, some new schemes, e.g., circular statistics (Levick and Thibos 1982;Thibos and Levick 1985) and the SDO-analysis based on Fast Fourier Transform (Worgotter and Eysel 1987;Worgotter et al 1990), have been suggested. It can be proven theoretically that the two schemes result in equivalent algorithms despite different primary ideas and mathematical tools adopted (cf.…”
Section: Introductionmentioning
confidence: 99%